Nekateri vidiki oskrbe kot večplastnega procesa in odzivi socialnega varstva na potrebe po oskrbi v Sloveniji - Krstulović, Gašper (Socialno delo, 2014)
The paper considers the question how recent developments in theory of care affect the responses of social care providers in Slovenia. Care work is a multi-layered process and includes physical, cognitive and emotional work. The effects of market liberalization on care work and responses of social care providers are analysed. Concepts of domestic assistance, personal assistance, institutional care and respite care are discussed and compared with new theoretical developments and research on care. The conclusion of the article deliberates on the multi-layered care for children with disabilities. The concept of respite care as an example of care provision that intertwines both physical and emotional support in introduced. The absence of public discourse about care in Slovenia is worrisome since it affects quality of received care and quality of work life for people providing care.
Keywords: socialno varstvo; skrbstveno delo; oskrba; institucionalno varstvo; kratkotrajna namestitev; Slovenia; Slovenija